Dampak Perkawinan Campuran Terhadap Pemeliharaan Anak - Basuki, Zulfa Djoko (UI Scholars Hub, 2021)
Nationality is a basic need for everyone who lives in this world because of its effect. Nobody can live without nationality. It gives protection and certainty to fulfill the needs of human being. At implementation level, nationality can bring some rights and some obligations. To convince it will run smoothly, nationality has its own rule and principle. It is different between one country and another but the principle can be categorized into two, which are ius sanguinis or ius soli. Indonesia bases its nationality rule or ius sanguinis principle, as embodied in Law Number 62 Years 1958 on Nationality. Unfortunately, ths Law is considered inappropriate for current development, especially for women and children in the fairness to gain their nationality. This article analyzes the points that must be evaluated and fixed, also gives some recommendations how to solve the problems.